1990
DOI: 10.1080/00103629009368293
|View full text |Cite
|
Sign up to set email alerts
|

A soil test for nitrogen availability in the northeastern United States

Abstract: A soil test for nitrogen availabilty to corn (Zea mays, L) has gained wide acceptance in the northeast region of the United States. The test involves sampling the surface 30 cm of soil during the early part of the growing season. The N0 3 -N present at that time is correlated with the probability of obtaining a yield increase by using sidedress nitrogen fertilizer. The test has been evaluated in 272 yr-site N response experiments in Vermont, Pennsylvania, Connecticut, New York, and New Hampshire. The various s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
1
2

Year Published

1992
1992
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 8 publications
3
71
1
2
Order By: Relevance
“…Besides the seed yield of the 0-N plot and the plant-available soil N supply, the use of real-time monitoring via plant analysis or soil mineral N testing might provide a more timely reflection of the crop N demand to guide the N fertilization in each specific condition. Li et al (2012) showed that the use of a soil plant analysis development (SPAD) meter was the most suitable method for rapidly diagnosing the N status in rapeseed; soil mineral N testing has been widely used for the specific N management of upland crops (Magdoff et al 1990;Cui et al 2008). Based on the differences between the results of soil mineral N tests before fertilization and the critical soil mineral N content during this period (Peng et al 2013), synthetic fertilizer is then applied to match crop N requirements in quantity and synchronize in time and space.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the seed yield of the 0-N plot and the plant-available soil N supply, the use of real-time monitoring via plant analysis or soil mineral N testing might provide a more timely reflection of the crop N demand to guide the N fertilization in each specific condition. Li et al (2012) showed that the use of a soil plant analysis development (SPAD) meter was the most suitable method for rapidly diagnosing the N status in rapeseed; soil mineral N testing has been widely used for the specific N management of upland crops (Magdoff et al 1990;Cui et al 2008). Based on the differences between the results of soil mineral N tests before fertilization and the critical soil mineral N content during this period (Peng et al 2013), synthetic fertilizer is then applied to match crop N requirements in quantity and synchronize in time and space.…”
Section: Discussionmentioning
confidence: 99%
“…This is also a practical difficulty with the test. For example, many dairy farmers grow corn and forage crops, and typically pre-sidedress nitrate test samples will need to be taken during a busy first-cut harvest window of the forage crops on these farms (Magdoff et al, 1990). In addition, collecting the soil samples in some environments is not easy, rendering the test unpopular in parts of the United States, such as in New England where stony soils are abundant.…”
Section: Pre-sidedress Nitrate Testmentioning
confidence: 99%
“…Although the goal in amenity turfgrass is not to maximize the yield, similar critical values between turf-type and forage-type grass yields suggest that the maximum growth response of perennial cool-season grasses, whether for forage or turfgrass use in our climate, will be reached at soil NO 3 -N concentrations approaching 10 to 15 mg kg . The crops that have been studied include silage corn (Magdoff et al, 1990;Fox et al, 1989;Meisinger et al, 1992;Klausner et al, 1993;Sims et al, 1995), field pumpkin (Cucurbita pepo L.) (Morris et al, 2000), sweet corn [Zea mays subsp. saccharata (Sturtev.)…”
Section: Clippings Dry Matter Yieldsmentioning
confidence: 99%